A prospective cohort study to assess the clinical profile of acute appendicitis and evaluate the combined use of modified Alvarado score and ultrasonography in a tertiary care center in India - Yadav GD; Nishant Saxena; Anju Yadav; Shraddha Verma; Mohd Arshad (Asian Journal of Medical Sciences, 2022)
Background: Acute appendicitis is one of the most common causes of acute abdomen presentation to the hospital. If not treated in time, it may lead to perforation. Alvarado score is a clinical scoring system used in the diagnosis of acute appendicitis. The score is based on laboratory findings, clinical symptoms, and signs. We stipulate that ultrasonography and modified Alvarado score (MAS) can be synchronously and concomitantly be used to reach a trustable diagnosis of acute appendicitis. Aims and Objectives: The aims of this study were to assess the clinical profile of acute appendicitis and evaluate the combined use of MAS and ultrasonography (USG) in a tertiary care center in India. Materials and Methods: This is a prospective observational study, in which a cohort of patients presenting with acute abdomen due to acute appendicitis to the department of general surgery (Out Patient Department and Emergency) of L.L.R. Hospital attached to G.S.V.M. Medical College, Kanpur and meeting specific inclusion criteria were sampled between October 2021 and January 2022. Results: Our study re-enforces and supports demographic findings of prevalence as well as clinical findings reported in the previous studies on acute appendicitis. Conclusion: CECT of the abdomen can prove to be financially straining for people seeking treatment at public health care centers in developing or underdeveloped countries. Our study suggests that USG can be concomitantly and synchronously be used with MAS to reach a trustable diagnosis without the need for a CECT of the abdomen.